1984
DOI: 10.2466/pr0.1984.54.3.783
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Role Conflict between Physicians and Nurse Practitioners

Abstract: This study examined the relationships between personal, job, and organizational factors and perceived role conflict between physicians and nurse practitioners. Data from 361 nurse practitioners showed that perceived conflict was significantly and negatively correlated with satisfaction, task characteristics, and instrumental leadership style of the supervisory physician. Significantly positive correlations were obtained between conflict and organizational size in terms of number of physicians and nurses in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A lack of understanding of nursing's role is exacerbated by fears of economic competition between physicians and nurse practitioners (Mechanic and Aiken 1982), and by physicians' inflexible definitions of the nurse's role (Chacko and Wong 1984). Katzman and Roberts (1988) find that nurse practitioners confront barriers to enacting an expanded role.…”
Section: Role Conflictsmentioning
confidence: 99%
“…A lack of understanding of nursing's role is exacerbated by fears of economic competition between physicians and nurse practitioners (Mechanic and Aiken 1982), and by physicians' inflexible definitions of the nurse's role (Chacko and Wong 1984). Katzman and Roberts (1988) find that nurse practitioners confront barriers to enacting an expanded role.…”
Section: Role Conflictsmentioning
confidence: 99%
“…Available studies point to the pivotal role of the physician in understanding the behaviour of other health care providers (4)(5)(6). The leadership style and receptivity of the physician seem to be major predictors of ancillary professions' ability to perform tasks successfully (8). Berggren (7), in a study of a Swedish health service setting, identified how professionals' claim to turf, their territoriality (non-physical), reduces co-operation.…”
Section: Research On Conflict In the Workplacementioning
confidence: 99%
“…Berggren (7), in a study of a Swedish health service setting, identified how professionals' claim to turf, their territoriality (non-physical), reduces co-operation. Organizational size and conflicts seem to be positively correlated, whereas gender has little to do with conflict (4,8). The attributional style of the individual professional, either external or internal, is related to self-0 Scandinavian University Press, 1999.…”
Section: Research On Conflict In the Workplacementioning
confidence: 99%
“…ISSN 0283-9318 management in conflict situations (6). The leadership style and receptivity of the physician seem to be major predictors of ancillary professions' ability to perform tasks successfully (8). Physician receptivity is important not just between professions, but even within the medical profession, as indicated by Fox (9) in his analysis of the rival perspectives on patients held by surgeons and anaesthetists.…”
Section: Research On Conflict In the Workplacementioning
confidence: 99%